Combination of anti-TNFα therapy and surgical resection for severe chronic intestinal rejection: A case report - Katrina Tan; Elizabeth Low; Graham Starkey; Khashayar Asadi; Adam Testro; Darren Wong (Intestinal Failure)
Background: Acute cellular rejection (ACR) is a well-recognised cause of graft failure in intestinal transplant (ITx) recipients. Management of ACR is with intravenous (IV) steroids, increased immunosuppression and T-cell depleting therapies. Use of alternative therapies such as anti-tumour necrosis factor alpha (TNFα) agents in steroid-refractory cases should be considered. Case report: A 44-year-old male who received a combined liver-intestinal transplant with ACR unresponsive to IV steroids and anti-thymocyte globulin (ATG), which evolved into chronic rejection (CR). His symptoms were predominantly obstructive with endoscopic similarities to stricturing Crohn’s disease. He was successfully managed with infliximab followed by segmental graft resection. With ongoing maintenance infliximab he has remained clinically well with enteral autonomy and no recurrence of rejection. Conclusion: Alternative therapies for management of severe ACR unresponsive to traditional management should be considered in ITx patients. There are increasing numbers of case reports to support the use of anti-TNFα therapy in these cases.